Can socio-demographics still play a role in profiling green consumers? A review of the evidence and an empirical investigation - Diamantopoulos, Adamantios; Schlegelmilch, Bodo B; Sinkovics, Rudolf R; Bohlen, Greg M (Journal of business research, 2003)
This paper explores whether socio-demographics still have a role to play in profiling green consumers. Following an interdisciplinary review of the literature, the second part of the paper attempts to address shortcomings identified in previous research. Specifically, hypotheses are developed concerning the relationship between six key socio-demographic variables and five valid and reliable measures of environmental consciousness. These hypotheses are subsequently tested on a large nationwide sample of British consumers and conclusions drawn on the utility of socio-demographic variables for profiling green consumers.